The problem of the diagnosis of early congenital syphilis: a case report - V. I. Surganova; N. V. Polyakova; N. K. Levchik; N. V. Zilberberg; T. A. Syrneva (Лечащий Врач)
Congenital syphilis is still a public health concern, and syphilis can go unnoticed in pregnant women, even in developed countries with active antenatal care. Currently, according to the International Classification of Diseases (ICD-10), early (in children under 2 years of age) and late congenital syphilis (in children over 2 years of age) are distinguished. Features of the clinical course of early congenital syphilis make it possible to divide it into early congenital syphilis of infancy (up to 1 year) and early childhood (from 1 to 2 years). The signs of congenital syphilis are diverse and a high index of suspicion must be maintained to make the diagnosis. Early congenital syphilis usually appears in the neonatal period and seldom later than 3-4 months of life and hardly ever in children older than one year of age. We report 20-month-old boy with congenital syphilis who presented bone lesions in the lower extremities and cutaneous eruptions and remained undiagnosed until his mother was diagnosed with secondary syphilis. The article also highlights the possible difficulties in diagnosing syphilis in children of early childhood.